1996
DOI: 10.1055/s-2007-997569
|View full text |Cite
|
Sign up to set email alerts
|

Sonographie von Orbitabodenfrakturen: Eine Alternative zur Computertomographie?*

Abstract: B-mode ultrasonography is a valuable and inexpensive technique to visualize orbital floor fractures. It should be employed in primary evaluation patients with suspected isolated orbital floor fractures prior to taking plain radiographs of the paranasal sinuses. Computed tomography should be used in suspected complex fractures and questionable orbital fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 1 publication
1
4
0
1
Order By: Relevance
“…[28][29][30][31][32][33] To obviate this concern, some investigators have suggested orbital ultrasonography as an alternative, with a sensitivity, specificity, positive-predictive value and negative-predictive value ranging from 85% to 95%, 57% to 100%, 57% to 100% and 60% to 91%, respectively. [10][11][12]15,16,18,19 In the present study, the corresponding values were 87.2%, 100%, 100% and 94.2%, respectively; suggesting a high diagnostic accuracy of ultrasonography in detecting orbital floor fractures. Using a recent cuttingedge ultrasonography equipment, larger sample size and CT-confirmed diagnoses for all patients are major advantages of the present study over the mentioned reports.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…[28][29][30][31][32][33] To obviate this concern, some investigators have suggested orbital ultrasonography as an alternative, with a sensitivity, specificity, positive-predictive value and negative-predictive value ranging from 85% to 95%, 57% to 100%, 57% to 100% and 60% to 91%, respectively. [10][11][12]15,16,18,19 In the present study, the corresponding values were 87.2%, 100%, 100% and 94.2%, respectively; suggesting a high diagnostic accuracy of ultrasonography in detecting orbital floor fractures. Using a recent cuttingedge ultrasonography equipment, larger sample size and CT-confirmed diagnoses for all patients are major advantages of the present study over the mentioned reports.…”
Section: Discussionsupporting
confidence: 52%
“…The available reports, however, are not uniform in terms of its accuracy, [11][12][13][14][15][16][17] probably because of imperfect methodologies and using outdated ultrasonography equipment in older series. [18][19][20] Another suggested alternative to conventional CT in detecting orbital fractures is CBCT. 21 The most prominent advantage of CBCT over conventional CT in maxillofacial imaging is lower patient radiation doses for the former.…”
Section: Introductionmentioning
confidence: 99%
“…The value of ultrasonography as a diagnostic tool for the detection of "bone" fractures (eg, in congenital hip dislocation, fractures of the radial or clavicular bone, or fractures of the ribs or skull) has been proven in various studies. [5][6][7][8] To our knowledge, only 4 studies [9][10][11][12] have dealt with the diagnosis of nasal fractures by ultrasound imaging. Danter et al an ultrasound device to investigate nasal fractures in 18 patients.…”
mentioning
confidence: 99%
“…Die Diagnose ist nur histologisch zu stellen, so daß bei verdächtiger Symptomatik (Lymphknotenvergrößerungen, dermale Papeln, dermatologische Erkrankungen (seborrhoisches Ekzem, M. Darier) und andere Erkrankungen im HNO-Bereich gedacht werden (Otitiden; Cholesteatome; physiologisch vergrößerte Antrumzellen im Mittelohr; HLK-Vergrößerungen anderer Genese, wie virale Lymphadenopathien, Kikuchi-Syndrom oder Metastasen anderer Neoplasien) [18,20,21,27]. Die Diagnose ist nur histologisch zu stellen, so daß bei verdächtiger Symptomatik (Lymphknotenvergrößerungen, dermale Papeln, dermatologische Erkrankungen (seborrhoisches Ekzem, M. Darier) und andere Erkrankungen im HNO-Bereich gedacht werden (Otitiden; Cholesteatome; physiologisch vergrößerte Antrumzellen im Mittelohr; HLK-Vergrößerungen anderer Genese, wie virale Lymphadenopathien, Kikuchi-Syndrom oder Metastasen anderer Neoplasien) [18,20,21,27].…”
Section: Kasuistikunclassified